Early-Phase Urine Output and Severe-Stage Progression of Oliguric Acute Kidney Injury in Critical Care - Huang, Haoquan; Bai, Xiaohui; Ji, Fengtao; Xu, Hui; Fu, Yanni; Cao, Minghui (Frontiers in Medicine, 2021)
Background: The relationship between urine output (UO) and severe-stage progression in the early phase of acute kidney injury (AKI) remains unclear. This study aimed to investigate the relationship between early-phase UO6−12h [UO within 6 h after diagnosis of stage 1 AKI by Kidney Disease: Improving Global Outcomes (KDIGO) UO criteria] and severe-stage progression of AKI and to identify a reference value of early-phase UO6−12h for guiding initial therapy in critical care. Methods: Adult patients with UO < 0.5 ml/kg/h for the first 6 h after intensive care unit (ICU) admission (meeting stage 1 AKI by UO) and UO6−12h ≥ 0.5 ml/kg/h were identified from the Medical Information Mart for Intensive Care (MIMIC) III database. The primary outcome was progression to stage 2/3 AKI by UO. After other variables were adjusted through multivariate analysis, generalized additive model (GAM) was used to visualize the relationship between early-phase UO6−12h and progression to stage 2/3 AKI by UO. A two-piecewise linear regression model was employed to identify the inflection point of early-phase UO6−12h above which progression risk significantly leveled off. Sensitivity and subgroup analyses were performed to assess the robustness of our findings. Results: Of 2,984 individuals, 1,870 (62.7%) with KDIGO stage 1 UO criteria progressed to stage 2/3 AKI. In the multivariate analysis, early-phase UO6−12h showed a significant association with progression to stage 2/3 AKI by UO (odds ratio, 0.40; 95% confidence interval, 0.34–0.46; p < 0.001). There was a non-linear relationship between early-phase UO6−12h and progression of AKI. Early-phase UO6−12h of 1.1 ml/kg/h was identified as the inflection point, above which progression risk significantly leveled off (p = 0.780). Patients with early-phase UO6−12h ≥ 1.1 ml/kg/h had significantly shorter length of ICU stay (3.82 vs. 4.17 days, p < 0.001) and hospital stay (9.28 vs. 10.43 days, p < 0.001) and lower 30-day mortality (11.05 vs. 18.42%, p < 0.001). The robustness of our findings was confirmed by sensitivity and subgroup analyses. Conclusions: Among early-stage AKI patients in critical care, there was a non-linear relationship between early-phase UO6−12h and progression of AKI. Early-phase UO6−12h of 1.1 ml/kg/h was the inflection point above which progression risk significantly leveled off.